Zeolites for food applications: A review. (April 2022) - Villa, Cristian C.; Valencia, Germán Ayala; López Córdoba, Alex; Ortega-Toro, Rodrigo; Ahmed, Shakeel; Gutiérrez, Tomy J.
Abstract: Zeolites have been little investigated for food applications, despite their chemical composition is similar to clays and clay minerals, which have been extensively analyzed for various applications, including food. Zeolites can be distinguished from clay materials, since the former have a porous microstructure characterized by intracrystalline cavities and channels, while the latter have a laminar microstructure. The goal of this review paper was to give a comprehensive perspective in terms of the different food applications found so far for zeolites, namely: antimicrobial materials, ethylene scavengers, fillers for food packaging materials, food nanoreactors, food substance sensors, immobilizers and stabilizers of active compounds and enzymes, molecular sieves for the pretreatment of food samples, as well as intelligent food contact materials. The main food applications from zeolites are related to their good properties as adsorbent materials, and these properties can be altered and tuned by ion exchange, surface organo-modification, among others, for a specific designed application. Zeolites for food applications have been investigated primarily as antimicrobial materials, concentrators of target analytes and sensors for food substances. However, the other potential food applications indicated above from zeolites are booming, since they are harmless materials recognized by various organizations. Graphical abstract: Image 1 Highlights: Zeolites are made up of microporous crystalline aluminosilicates. Zeolites are excellent adsorbent materials. Zeolites can be used for sample preparation. Zeolites can also be employed as antimicrobial materials and ethylene scavengers. Zeolites-based nanoreactors, sensors and stabilizers are emerging food applications.